Biallelic Variants in CFAP61 Cause Multiple Morphological Abnormalities of the Flagella and Male Infertility - Ma, Ao; Zeb, Aurang; Ali, Imtiaz; Zhao, Daren; Khan, Asad; Zhang, Beibei; Zhou, Jianteng; Khan, Ranjha; Zhang, Huan; Zhang, Yuanwei; Khan, Ihsan; Shah, Wasim; et al. (Frontiers in Cell and Developmental Biology, 2022)
Multiple morphological abnormalities of the flagella (MMAF) can lead to male infertility due to impaired sperm motility and morphology. Calmodulin- and spoke-associated complex (CSC) are known for their roles in radial spoke (RS) assembly and ciliary motility in Chlamydomonas, while the role of CFAP61, a mammalian ortholog of the CSC subunits, in humans is yet unknown. Here, we recruited three unrelated Pakistani families comprising of 11 infertile male patients diagnosed with MMAF. CFAP61 variants, c.451_452del (p.I151Nfs*4) in family 1 and c.847C>T (p.R283*) in family 2 and 3, were identified recessively co-segregating with MMAF phenotype. Transmission electron microscopy analyses revealed severe disorganized axonemal ultrastructures, and missings of central pair, RSs, and inner dynein arms were also observed and confirmed by immunofluorescence staining in spermatozoa from patients. Interestingly, although the interactions with other CSC subunits, Calmodulin, CFAP251 and CFAP91, were retained by the predicted truncated CFAP61 proteins, CFAP251 was not detected in sperm tails of the patient, which suggested the loss of functional CSC in sperm flagella. Altogether, our findings report that homozygous variants in CFAP61 are associated with MMAF and male infertility, demonstrating the essential role of this gene in normal sperm flagellum structure in humans.